Plasma Levels of C1q/TNF-Related Protein 1 and Interleukin 6 in Patients With Acute Coronary Syndrome or Stable Angina Pectoris. (February 2015) - Tang, Jun-Nan; Shen, De-Liang; Liu, Cong-Lin; Wang, Xiao-Fang; Zhang, Li; Xuan, Xue-Xi; Cui, Ling-Ling; Zhang, Jin-Ying
Abstract: Background: C1q/TNF-related protein 1 (CTRP-1), a novel adipocyte factor, may participate in the mechanisms of metabolism and inflammation. Interleukin 6 (IL-6) is a proinflammatory cytokine that is correlated with the severity of coronary heart disease (CHD). In this study, we focused on the levels of CTRP-1 and IL-6 in patients with CHD. Methods: Circulating CTRP-1 and IL-6 levels were measured using enzyme-linked immunosorbent assay in 81 patients with acute coronary syndrome (n = 41) or stable angina pectoris (n = 40). CTRP-1 and IL-6 levels were also examined in 30 healthy individuals (control group). We examined the correlations between the levels of CTRP-1 and IL-6 and cardiac risk factors in CHD. Logistic regression analysis was performed to screen for factors that predict CHD. Results: Both CTRP-1 and IL-6 concentrations were increased in the acute coronary syndrome or stable angina pectoris group compared with the control group ( P < 0.01). Both plasma levels of CTRP-1 and IL-6 in the single-, double- and triple-vessel lesion group were higher compared with the control group ( P < 0.01). CTRP-1 levels were positively correlated with IL-6 (r = 0.667, P < 0.01) and high-sensitivity C-reactive protein levels (r = 0.520, P < 0.01) and negatively correlated with HDL-C (r = −0.432, P < 0.01). The logistic regression analysis showed that increases in CTRP-1 and IL-6 levels may be powerful predictors of CHD. Conclusions: The variation of plasma CTRP-1 and IL-6 concentrations may play an important role in reflecting the degree of inflammation in CHD and the severity of coronary arterial atherosclerosis. This potential suggests that evaluating CTRP-1 and IL-6 in combination may aid in predicting the occurrence of CHD.